Animal protein intake at 12 months is associated with growth factors at the age of six. (21st February 2014) - Thorisdottir, Birna; Gunnarsdottir, Ingibjorg; Palsson, Gestur Ingvi; Halldorsson, Thorhallur Ingi; Thorsdottir, Inga
Abstract Aim To study the associations between protein intake from different sources with anthropometry and serum insulin‐like growth factor 1 (IGF‐1) in infancy and childhood. Methods Children (n = 199) born in Iceland were followed up to six years of age. Their intake of various animal proteins and vegetable protein was calculated from weighed food records at 12 months and 6 years. Information about their weight and height at birth, 12 and 18 months, and 6 years was gathered. Serum IGF‐1 was measured at 12 months and 6 years. Results At the age of six, children in the highest quartile for animal protein intake at 12 months (≥12.2% of total energy) had 0.8 kg/m2 (95% CI = 0.1, 1.5) higher body mass index (BMI) than children in the lowest quartile (<7.6% of total energy). They were also heavier and longer in infancy and childhood. At 12 months, dairy protein intake as a percentage of total energy was associated with IGF‐1 in six‐year‐old girls, β = 5.4 μg/L (95% CI = 2.5, 8.2). Conclusion High animal protein intake in infancy, but not vegetable protein intake, was associated with accelerated growth and higher BMI in childhood. Dairy protein intake in infancy may be positively associated with linear growth and also with IGF‐1 in six‐year‐old girls.